Videotaped Unannounced Standardized Patient Encounters to Evaluate Interpersonal and Communication Skills in Emergency Medicine Residents. Issue 4 (15th November 2019) - Chung, Arlene S.; Bogoch, Sally; Mody, Shivani; Smith, Colleen; Pushkar, Illya; Drapkin, Jefferson; Saloum, David
Abstract: Background: Communication and interpersonal skills are important for effective patient care but are difficult to measure. Unannounced standardized patient encounters (USPEs) have the benefit of providing a standardized situation and provide a representation of usual care rather than best behavior, while also allowing for video recording without violating patient privacy. We conducted a feasibility pilot study to examine the use of videotaped USPEs in resident education of interpersonal and communication skills and specifically empathy. Methods: This was a pilot study conducted at an urban community teaching hospital. About 16 first‐year emergency medicine engaged in four videotaped USPEs during their normal clinical shifts during 1 academic year. All visible recording equipment was concealed from the residents. The standardized patients completed two assessment forms after each encounter to measure empathy. Results: All 16 residents engaged in four videotaped USPEs for a total of 64 encounters. Conclusions: We were able to successfully demonstrate the feasibility of using USPEs for assessment of resident interpersonal and communication skills.